DESIGN AND IMPLEMENTATIONOFNETWORK SWITCH FOR CONTROLLER COMMUNICATION - Mr Sreepada Ravikumar; S Hemasree (Utilitas Mathematica, 2025)
This project aims to research and analyse the capabilities of Controller Area Network (CAN) communication systems, a robust protocol widely utilized in industrial and automotive applications. By exploring the scalability, reliability, and real-time communication capabilities of CAN, the study seeks to address its limitations in modern applications requiring higher band width and connectivity. To bridge this gap, the project proposes the design and development of a low-power, cost-efficient Ethernet switch tailored to meet the specific requirements of industrial automation and automotive systems. The proposed Ethernet switch will serve as a seamless interface between traditional CAN networks and Ethernet- based systems, enabling higher data rates, increased node capacity, and enhanced diagnostic capabilities without compromising the real-time performance critical to these domains. Key objectives include minimizing power consumption, reducing production costs, and ensuring compatibility with existing CAN and Ethernet standards. The deliverables of the project include a comprehensive analysis of CAN systems, design optimization of the Ethernet switch, and testing the prototype for industrial and automotive applications. This research promises to contribute significantly to the evolution of communication systems, aligning with the growing demand for Industry 4.0 and connected vehicle ecosystems.